Recovering Individual Genomes from Metagenomes Using MaxBin 2.0. Issue 5 (7th May 2021) - Wu, Yu‐Wei; Singer, Steven W.
Abstract: It is critical to identify individual genomes from microbiomic samples in order to carry out analysis of the microbes. Methods based on existing databases, however, may have limited capabilities in elucidating and quantifying the microbes due to the largely unidentified microbial species in natural or human‐associated environments. We thus developed a database‐free method, MaxBin 2.0, to aid in the process of recovering microbial genomes from metagenomes in a de novo manner. The recovery of individual genomes allows analysis of the microbiome in terms of a collection of microbial genomes so that one can understand the functional roles of each species. The data of individual microbes may then be analyzed collectively to untangle the interactions between different microbial organisms. By reporting the genome abundance information for co‐assembled metagenomes, one may also identify which microorganisms dominate the microbiome and which species may co‐occur from the MaxBin 2.0 results. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Recovering genomes from one shotgun metagenome with coverage information Basic Protocol 2 : Recovering genomes from one shotgun metagenome without coverage information Basic Protocol 3 : Recovering genomes given multiple shotgun metagenomes with coverage information for each metagenome Basic Protocol 4 : Recovering genomes given multiple shotgun metagenomes without coverage information Support Protocol 1 : MaxBin installation Support Protocol 2 : Assembling and co‐assembling NGS reads